Sensitizing Surgeons to Their Outcome Has No Measurable Short-term Benefit. Issue 5 (November 2017) - Cauchy, Francois; Farges, Olivier; Vibert, Eric; Boleslawski, Emmanuel; Pruvot, Francois René; Regimbeau, Jean Marc; Mabrut, Jean Yves; Scatton, Olivier; Adham, Mustapha; Laurent, Christophe; Grégoire, Emilie; Delpero, Jean Robert; et al.
Abstract : Objective: Investigate if involving surgeons in outcome prediction-research and having them use a dedicated Electronic-Health-Record that provides feedback, improves patients' outcome. Background: Improvement of clinical outcome mainly relies on the declaration of adverse events, identification of their predictors, self-assessment, and feedback. Methods: Thirteen French Hepato-Pancreato-Biliary-centers made commitment to include all patients undergoing elective hepatectomies in an observational study. Each center was given access to a dedicated website, where perioperative data were prospectively collected. The website provided real-time individual and comparative feedback of outcome and was also intended to perform prognostication studies. The hypothesis was that by using this strategy, the length-of-stay would be reduced by 10%. Power-calculation implied the inclusion of 1720 patients. Secondary endpoints were 90-day mortality, severe morbidity, and the comprehensive-complication index. Results: Only 5 of the 13 participating centers were fully compliant in enrolling their patients and the inclusion period was extended by 1-year (October 2012–October 2015) to meet the objective. During this period, the collaborative group published 9 studies based on the study data (median impact factor = 8.327) that identified quantitative clinical variables, qualitative clinical variables, and nonclinical variables influencing outcome. For patients enrolled by the 5 active centers (n = 1752), there was no improvement in length of stay (13.3 vs 12.4 days, P = 0.287), severe complications (23.6 vs 20.5%, P = 0.134), the complication comprehensive index (24.0 vs 24.9, P = 0.448), mortality (4.1 vs 3.9%, P = 0.903), or unplanned readmissions (7.2 vs 8.4%, P = 0.665), even after adjusting for confounders. Conclusion: Simply sensitizing surgeons to their outcome has no measurable short-term clinical benefit.